2023
DOI: 10.3390/microorganisms11020426
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cellulase or Lactiplantibacillus plantarum on the Ensiling Performance and Bacterial Community in Mixed Silage of Alfalfa and Leymus chinensis

Abstract: The objective of this study was to evaluate the effects of Lactiplantibacillus plantarum or cellulase on the fermentation characteristics and bacterial community of mixed alfalfa (Medicago sativa L., AF) and Leymus chinensis (LC) silage. The harvested alfalfa and Leymus chinensis were cut into 1–2 cm lengths by a crop chopper and they were thoroughly mixed at a ratio of 3/2 (wet weight). The mixtures were treated with no addition (CON), Lactiplantibacillus plantarum (LP, 1 × 106 cfu/g fresh material), cellulas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 61 publications
6
6
1
Order By: Relevance
“…In our study, the total yeast count of the alfalfa plant was determined as Log10 5.66 cfu/g and the mold count as Log10 4.04 cfu/g. These yeast values are higher than the values reported by Wang et al (2023) and Si et al (2023) in their studies, while the mold value of Wang et al (2023) is lower than our study. The yeast and mold count of Silva et al (2020) in alfalfa plants are similar to our study.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…In our study, the total yeast count of the alfalfa plant was determined as Log10 5.66 cfu/g and the mold count as Log10 4.04 cfu/g. These yeast values are higher than the values reported by Wang et al (2023) and Si et al (2023) in their studies, while the mold value of Wang et al (2023) is lower than our study. The yeast and mold count of Silva et al (2020) in alfalfa plants are similar to our study.…”
Section: Discussioncontrasting
confidence: 94%
“…When the data was analyzed, the LAB count of the fresh alfalfa plant was determined as Log10 4.38 cfu/g. This value was higher than the value reported by Sun and Yang (2021), lower than the value reported by Silva et al (2020), and Wang et al (2023), and similar to the value reported by Si et al (2023). A meta-analysis by Oliveira et al (2017) : Values with different letters in the same column were found to be different (P<0.05); NH 3 -N/TN: Ammonia nitrogen, CO 2 : Carbondioxide g/kg DM, LA: Lactic acid g/kg DM, AA: Acetic acid g/kg DM, PAYMV: Post aerobic yeastmold values.…”
Section: Discussionsupporting
confidence: 77%
“…Ensiling systems require low pH for feed preservation and inhibiting harmful microorganisms and molds ( Zhang et al, 2022 ). This study aligns with Si et al (2023) , demonstrating an initial rapid pH drop in early silage fermentation, continuing as fermentation progressed. The control silage’s pH (4.03) at 56 days was slightly lower than the pH (4.44) reported by Kizilsimsek et al (2017) for 60-day corn and soybean silage, likely due to higher WSC content in the whole-plant corn silage.…”
Section: Discussionsupporting
confidence: 88%
“…Lactobacillus plantarum is a homofermentative LAB favored in silage production, metabolizing WSC in silage to lactic acid and rapidly lowering pH to inhibit yeast and mold growth ( Mu et al, 2020 ). Inoculation with L. plantarum in mixed alfalfa and Leymus chinensis silage improves fermentation quality by increasing LA content and reducing pH and NH 3 -N content ( Si et al, 2023 ). In contrast, L. buchneri , a heterofermentative LAB, enhances silage’s aerobic stability by converting LA into acetic acid (AA), thereby inhibiting filamentous fungi growth ( Yin et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this result may be associated with the reduction in effluent production by lactobacillus action that includes approximately 8% DM [26]. In addition, supplementation of L. plantarum is beneficial for the homo-fermentation of silage and can inhibit decomposition in organic substances induced by inadequate production of lactic acid [27], which are conducive to decreasing the nutritional loss. WSC is an important fermentation substrate for lactic acid bacteria.…”
Section: Discussionmentioning
confidence: 99%